2020
DOI: 10.31616/asj.2020.0034
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Implant Failure in Spinal Metastasis Surgery

Abstract: To investigate the incidence of symptomatic and asymptomatic implant failure in spinal metastasis surgery and identify potential risk factors. Overview of Literature: Surgical stabilization with instrumentation is an established method for the treatment of spinal metastasis. However, very few studies have investigated the incidence and risk factors for implant failure after spinal instrumentation surgery for the treatment of spinal metastasis. Methods: This study recruited 88 patients who received surgical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Seven studies [ 3 6 , 8 , 11 , 18 ] compared the spinal fixation failure rate between the older and younger subgroups. Values of I 2 = 0.0% and p = 0.945 were obtained after the OR values of the failure rate were merged, indicating that no heterogeneity existed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies [ 3 6 , 8 , 11 , 18 ] compared the spinal fixation failure rate between the older and younger subgroups. Values of I 2 = 0.0% and p = 0.945 were obtained after the OR values of the failure rate were merged, indicating that no heterogeneity existed.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 studies (including subgroups) [ 3 6 , 8 , 11 , 18 ] assessed the association between radiotherapy and failure rate. Values of I 2 = 56.0% and p = 0.415 were obtained after the OR values of the failure rate were merged, indicating that heterogeneity existed.…”
Section: Resultsmentioning
confidence: 99%
“…But some scholars believed that implant failure had nothing to do with radiotherapy. For example, Wong et al 25 reported the occurrence of IF in 9(10.2%) of their 88 metastatic cancer cases and therefore believed that radiotherapy either before or after spinal operation was associated with a reduced incidence of implant failure. Some studies reported that the affected vertebra became recalcified 1–2 months after destruction of tumor cells by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 ] A common typical complication after instrumentation addressed by various authors is loosening of the screws with related material failure, with a range from 1% to 15% up to 63%. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%